APPLICATION OF THE CONTEXTUAL TEACHING AND LEARNING (CTL) APPROACH TO INCREASE STUDENT LEARNING OUTCOMES OF CLASS IV STUDENTS SDN 167 PEKANBARU - Fedrik Sentosa; Gustimal Witri; Eddy Noviana (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2020)
This study was based on the low learning outcomes of social studies in fourth-grade students at SDN 167 Pekanbaru. Of the 20 students, only 9 students (45%) achieved minimum completeness, while the average student learning outcomes were 60.24. To overcome this learning problem, classroom action research is carried out by applying the contextual teaching and learning (CTL) approach. The purpose of this study is to improve social studies learning outcomes by applying the CTL approach. This research is a classroom action research conducted in the fourth grade SDN 167 Pekanbaru with a total of 20 students. This research was conducted in two cycles, the data collection techniques used were observation and written tests. The analysis technique used is a descriptive analysis of data on teacher and student activities and social studies learning outcomes. The results of the study state that the application of the CTL approach can improve the activities of teachers and students as well as social studies learning outcomes. This is evidenced by (1) teacher activities in the first cycle of the first meeting amounted to 50.00%, in the first cycle of the second meeting was 64.28%, in the second cycle the first meeting was 78.57% and in the second cycle II was 92.86%; (2) the activities of students in the first cycle of the first meeting were 57.14%, in the first cycle of the second meeting it was 67.85%. In the second cycle, the meeting I was 75.00% and in the second meeting cycle II was 89.28%; and (3) student learning outcomes have increased in the pre-cycle number of students who completed 9 students, in the first cycle became 12 students, in the second cycle became 17 students. The increase in the average learning outcomes from the basic score is 60.25 to 68.25 in the first cycle and 78.50 in the second cycle. Based on the results of this study, the application of the contextual teaching and learning (CTL) approach can improve learning outcomes in social studies subjects in grade IV SDN 167 Pekanbaru.